The Impatient Patient - Bereczky, Tamás (Socio.hu Társadalomtudományi Szemle, 2013)
Novel forms of knowledge production and dissemination increasingly extend to the involvement of civil society. This research looks at the role of the community of people living with HIV (PLH) in biomedical research and pharmaceutical development by tracing the evolution of such involvement from anger to activism to scientific contributions. The institutional review of the European Community Advisory Board (ECAB)2 has examined the history, working models, relevance, and future perspectives of the organisation. Semi–structured interviews have been conducted with organisation members and stakeholders to explore the history of ECAB and its role in scientific research. The concept and role of the “expert patient” are discussed. This paper emphasises the role of expert patients and their organisations in the production of knowledge with recommendations to ease the burden on health care institutions, reduce stigmatisation and discrimination, and to add aspects of the ‘consumers’ of knowledge to the process of knowledge production. The triple–helix model of knowledge production is revisited, and the adoption of a quadruple–helix model is proposed that includes civil society (the patient community) in the process of knowledge production and distribution. On a more general level, some conclusions are drawn as to how the empowerment of patients may in turn lead to a deepening and widening of democratic processes through increased awareness of citizens of their rights. A model of transition from expert patient to empowered citizen is proposed. KEYWORDS HIV, HIV/AIDS, HIV activism, sociology of knowledge, patient involvement, patient empowerment, Triple Helix, EATG, ECAB